EP1201 Laparoscopy versus laparotomy for surgical treatment of obese women with endometrial cancer: a cost-benefit comparative analysis. (1st November 2019) - Capozzi, VA; Cianciolo, A; Pugliese, M; Gambino, G; Sozzi, G; Armano, G; Monfardini, L; Gaiano, M; Ceni, V; Merisio, C; Berretta, R
Abstract : Introduction/Background: Obesity represents a major health problem. Several studies reported that morbid obesity is associated with an 81% greater health care expenditure per capita compared with normal weight adults in the US. Although many articles have investigated costs of laparoscopic versus open approach for endometrial cancer, very few data are available in selected population of patients, such as obese women. The aim of this study has been to evaluate pre-, intra- and post-operative costs in obese women affected by endometrial cancer comparing laparoscopic versus open abdominal surgery. Methodology: Economic expenditure in pre-operative, intra-operative and post-operative phases of the selected patients was evaluated. Costs were analyzed for all blood tests, instrumental examinations, consultations, operating materials, drugs, gynecological examinations, hospital stay, intensive care hospitalization and management of operative complications. Results: The average length of stay was longer for patients operated by laparotomy with an almost double median hospitalization cost in the open abdominal group compared to the laparoscopic group (€ 4805.37 vs. € 2589.25; p<0.0001). Evaluation by another specialist (cardiologist, diabetologist, internist) was necessary in 30.9% of laparotomies versus 10.4% of laparoscopies (p=0.003). Antibiotic and pain-relief therapies resulted in a significantly higher cost for the open abdominal than for the minimally-invasive approach (p=0.027). Considering all the pre-, intra- and post-operative course, the expenses for an obese patient operated by laparoscopy was € 4412.41 vs. € 7323.17 by open surgery. Conclusion: This study shows that in obese patients with endometrial cancer, minimally invasive surgery is more advantageous both in terms of costs and post-operative complications. Laparoscopic surgery in obese patients allows an economic saving of about 60% less than open surgery. Disclosure: Nothing to disclose